2022
DOI: 10.1111/famp.12739
|View full text |Cite
|
Sign up to set email alerts
|

How effective are ACF‐funded couple relationship education programs? A meta‐analytic study

Abstract: Since 2006, the U.S. Administration for Children and Families (ACF) has allocated $1.2 billion to a Healthy Marriage and Relationship Education (HMRE) policy initiative that provides grants to community organizations to support relationship education (RE) services for lower income couples and individuals. The policy aim was to help disadvantaged couples and individuals form and sustain healthy, stable relationships and marriages. A significant body of research on the effectiveness of these programs has now acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 49 publications
3
20
1
Order By: Relevance
“…Furthermore, parental conflict is associated with long‐term negative outcomes for children (Cummings & Davies, 1994; Cummings et al, 2015; Grych & Fincham, 1990). Although the program reduced conflict for couples, the size of the significant effect was small, which is consistent with small effects that have been observed in other rigorous randomized trials of programs funded by the ACF initiative (Hawkins et al, in press).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, parental conflict is associated with long‐term negative outcomes for children (Cummings & Davies, 1994; Cummings et al, 2015; Grych & Fincham, 1990). Although the program reduced conflict for couples, the size of the significant effect was small, which is consistent with small effects that have been observed in other rigorous randomized trials of programs funded by the ACF initiative (Hawkins et al, in press).…”
Section: Discussionsupporting
confidence: 84%
“…A more recent meta‐analysis of studies in the ACF program context suggested that the effects among couples at varying levels of disadvantage (high or low, etc.) may be similar, but the authors acknowledge important confounds in testing this question (Hawkins et al, in press). Amato re‐examined the data for the 15‐month follow‐up in the BSF study and found that sociodemographic risk moderated the effects, with significant impacts on relationship quality for those at greater sociodemographic risk (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Both relationship adjustment and individual distress may be conceptualized as global or general outcomes, which may explain the positive change that both treatment and waitlist control groups experienced at 30 days, but did not sustain across either group over time. The non‐significant findings for individual distress and relationship adjustment are inconsistent with previous randomized trials of relationship education (Hawkins et al, 2022; Roddy et al, 2020). However, there are some differences among the studies that should be considered.…”
Section: Discussioncontrasting
confidence: 84%
“…The significant intervention effects on the rate of positive change in dyadic coping and emotion regulation add to the growing body of literature that support relationship education as an efficacious intervention for couples with low‐income. Hawkins et al (2022) conducted a meta‐analysis among RE intervention studies funded specifically by the Administration for Children and Families (the same funder for this study). They identified small, positive, intervention effects on relationship quality, relationship skills, mental health, and co‐parenting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation